Disasters: a historical and social view for risk management - Ferradas Mannucci, Pedro (2020)
The article is an approximation to the social historical dimension of risks and disasters throughout our Republican History. It analyzes, based on 23 relevant cases that occurred in five periods of history, how the social, demographic, economic and political dynamics influenced such disasters and how they determined economic, political, social and institutional changes; It concludes with some final reflections that include changes in approaches and strategies in the face of disasters and current challenges. It stands out how in the 19th century the economic precariousness, political crises, and the weak presence of the State were decisive; in the first three decades of the 20th century, the strategies to face epidemics and, since the 1940s, the greatest impact of disasters on growing cities, as well as the reconstructions promoted by the State; In the period 1970-2010, the changes and contexts that originate and affect the development of the National Civil Defense System are surveyed; and since 2011, those that gave rise to the National Risk Management System in training and its current challenges.